2022
DOI: 10.4103/atm.atm_469_21
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and recommendations for the management of asthma in the Middle East and Africa

Abstract: Clinical presentation of asthma is variable, and its diagnosis can be a major challenge in routine health-care practice, especially in low-and-middle-income countries. The aim of asthma management is to achieve optimal asthma control and to reduce the risk of asthma exacerbations and mortality. In the Middle East and in Africa (MEA), several patient- and physician-related factors lead to misdiagnosis and suboptimal management of asthma. A panel of experts comprising of specialists as well as general health-car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 72 publications
0
6
0
1
Order By: Relevance
“…This is further seen with the low levels of inhaled corticosteroids (6.7–17%) and 73% of doctor-diagnosed/suspected asthma not using any inhaler documented 6 31. Over-reliance on short-acting beta agonist inhalers per se is also a barrier to appropriate care 32. A preference for oral over inhaler-administered medications and widely held concerns that metred dose inhalers were addictive and harmful identified have been noted previously 10 18.…”
Section: Discussionmentioning
confidence: 99%
“…This is further seen with the low levels of inhaled corticosteroids (6.7–17%) and 73% of doctor-diagnosed/suspected asthma not using any inhaler documented 6 31. Over-reliance on short-acting beta agonist inhalers per se is also a barrier to appropriate care 32. A preference for oral over inhaler-administered medications and widely held concerns that metred dose inhalers were addictive and harmful identified have been noted previously 10 18.…”
Section: Discussionmentioning
confidence: 99%
“…42 In addition, another study discussed the recommendations for the management of asthma along with regional adaptations of international guidelines for the MENA. 43 Patients with both types of diseases were interviewed to assess the technical use of pressurized metered dose inhalers and it was shown that many patients with respiratory diseases were not properly using their medications which requires intervention of their healthcare professionals. 44 Studies that focused on mental/psychological health COVID-19 restriction measures, such as social isolation, have affected the mental and psychological wellbeing of millions of people worldwide.…”
Section: Studies That Focused On Other Respiratory Diseases (Not Rela...mentioning
confidence: 99%
“…Через 3 місяці після впровадження експертних рекомендацій вдалось знизити число призначень монотерапії БАКД на 40 % та на 20 % збільшити число призначень комбінації ІКС-формотерол. І такі зміни, в свою чергу, призвели до збільшення на 55 % числа пацієнтів з контрольованою астмою та до зниження на 35 % числа пацієнтів, що потребували невідкладної допомоги [25][26][27][28][29].…”
Section: огляд літературиunclassified